The Science of Nasikh Mansukh and Its Future: The Inspiration of Richard Bell - Imam Ahmad Abi Abdillah; Nazli Badrul ‘Aini Ramdhani; Rabiatul Adawiyah; Asrar Mabrur Faza (Aslim: Journal of Education and Islamic Studies, 2025)
This research discusses the thoughts of the leading orientalist, namely Richard Bell, who lived at the end of the 19th and early 20th centuries, regarding his biography, his works, the approach he used and his thoughts on texts in the Koran.  This research is library research which was carried out to comprehensively study various literature and writings related to research. Literature study involves collecting information from sources such as books, journals and other relevant publications. The results of Nasakh Mansukh's theory and also Richard Bell's theory of Koranic chronology carry out a reconstruction of the theory of Muslims which has experienced stagnation since the time of classical scholars. Therefore, this article wants to discuss, examine and examine Richard Bell's theory in more depth along with its evidence in the verses of the Koran and its implications for the discourse on the study of the Koran. And it is hoped that the results of this research will provide new insights into the study of orientalism and enrich critical discussions about issues related to orientalism and Islamic studies.